The The Prevalence of Hard Ticks Infesting Humans in the South Bačka District: Association of Age and Infestation Localization with Tick Developmental Stages - Stevanoska, Silvana; Simin, Verica; Bogdan, Ivana; Gazibara, Dragana; Mijatović, Dragana; Stojšić, Andrea; Banović, Pavle (PONS - medicinski časopis, 2025)
ABSTRACT    Objective. The aim of this study was to determine the prevalence of different tick species infesting humans, to assess the correlation between patient age and the body region affected by the infestation, as well as to analyze the number of human infestations during the period from January 1, 2023, to December 31, 2023.Methods. The study included patients residing in the South Bačka District who visited the Pasteur Institute with either a removed or attached tick. Patients were divided into eight age categories: 1–10 years, 11–20 years, 21–30 years, 31–40 years, 41–50 years, 51–60 years, 61–70 years, and 71–80 years. The study analyzed associations between age categories and the affected body regions (head and neck, upper extremities, lower extremities, torso, and genital area), the number of removed ticks, and the developmental stages of ticks (adult, nymph, larva).Results. A total of 502 ticks were collected during the study period. Six tick species were identified, with Ixodes ricinus being the most prevalent (460/502; 91.63%). Of the total ticks collected, 252 (50.19%) were nymphs, while 205 (40.83%) were adults. Regression analysis revealed a statistically significant correlation between the frequency of infestation of arms, legs, and the genital region and the age of participants. Risk analysis showed a statistically significant difference in the likelihood of nymph infestations compared to adults in patients aged 1–10 years, with the probability of nymph infestation being nearly 1.5 times higher.Conclusion. The results of this study highlight the dominance of Ixodes ricinus among ticks infesting humans in the South Bačka District, with nymphs being the most common developmental stage. A significant correlation was observed between the age of patients and the localization of infestations on the body, as well as an increased risk of nymph infestations in children aged 1–10 years. These findings provide valuable insights into the epidemiological characteristics of tick infestations, contributing to better planning of preventive measures and public education on tick-borne risks and protection.
Keywords: Keywords: tick, Lyme borreliosis, risk factors, Serbia.